2012
DOI: 10.1210/jc.2012-1836
|View full text |Cite
|
Sign up to set email alerts
|

Polycystic Ovary-Like Abnormalities (PCO-L) in Women with Functional Hypothalamic Amenorrhea

Abstract: PCO-L in FHA is a frequent and usually incidental finding of unclear significance, as in controls. The association of PCO-L with hypothalamic amenorrhea should not lead to a mistaken diagnosis of PCOS.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
35
0
3

Year Published

2013
2013
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 53 publications
(43 citation statements)
references
References 26 publications
5
35
0
3
Order By: Relevance
“…However, the diagnosis of PCOS can be subjective, because counting the ovarian follicular number and measuring the ovarian volume using ovarian ultrasound are technique-dependent and because obtaining standardized measurements is difficult. The number of follicles and the size of the ovary measured by ovarian ultrasound may overlap in women with and without PCOS, and PCOM has been reported frequently in women without PCOS [3]. Moreover, there is currently no consensus on the most appropriate androgen to measure for PCOS diagnosis, and diverse androgen cutoff values have been suggested for the determination of biochemical hyperandrogenemia and diagnosis of PCOS because direct immunoassay methods can be highly inaccurate for the measurement of testosterone when its level is at the lower end of the female range [4].…”
Section: Introductionmentioning
confidence: 99%
“…However, the diagnosis of PCOS can be subjective, because counting the ovarian follicular number and measuring the ovarian volume using ovarian ultrasound are technique-dependent and because obtaining standardized measurements is difficult. The number of follicles and the size of the ovary measured by ovarian ultrasound may overlap in women with and without PCOS, and PCOM has been reported frequently in women without PCOS [3]. Moreover, there is currently no consensus on the most appropriate androgen to measure for PCOS diagnosis, and diverse androgen cutoff values have been suggested for the determination of biochemical hyperandrogenemia and diagnosis of PCOS because direct immunoassay methods can be highly inaccurate for the measurement of testosterone when its level is at the lower end of the female range [4].…”
Section: Introductionmentioning
confidence: 99%
“…The existence of PCOM is quite frequent in normo-ovulatory women from the general population, including normo-ovulatory women with no hyperandrogenism [39][40][41][42]. In FHA, Robin et al [17] identified (by cluster analysis) three groups of patients, depending on serum AMH level (as a surrogate for PCOM). The first two groups [normal serum AMH level (52%) and moderate increase (about twofold) of serum AMH level (38%)] were in line with findings in female controls.…”
Section: Discussionmentioning
confidence: 99%
“…Besides PCOS, PCOM may also be observed as an isolated feature in about 30% of normal women and in patients with FHA [17]. The association between FHA and PCOM has been poorly described in the literature and the studies are heterogeneous (variable diagnostic criteria of FHA and PCOM, confusion between hypogonadotropic hypogonadism and FHA, inconsistent LH levels, small series or case reports) and as a result, the conclusions are contradictory [18][19][20][21][22][23][24][25][26][27].…”
Section: Introductionmentioning
confidence: 99%
“…Concerns have been raised that the more inclusive Rotterdam definition may lead to a mistaken diagnosis of PCOS in women with functional hypothalamic amenorrhoea if the hypothalamic origin of the menstrual disorder is not recognized . Due to fluctuations in the hypothalamic dysfunction, many women with hypothalamic amenorrhoea have levels of gonadotrophins within the normal range and are thus classified as WHO Group II.…”
Section: Discussionmentioning
confidence: 99%
“…6 Concerns have been raised that the more inclusive Rotterdam definition may lead to a mistaken diagnosis of PCOS in women with functional hypothalamic amenorrhoea if the hypothalamic origin of the menstrual disorder is not recognized. 16,17 Due to fluctuations in the hypothalamic dysfunction, many women with hypothalamic amenorrhoea have levels of gonadotrophins within the normal range 18 and are thus classified as WHO Group II. Although this subgroup should be distinguished from normogonadotrophic women with a primarily ovarian dysfunction, the combination of chronic anovulation and PCOM may imply a diagnosis of PCOS.…”
Section: Discussionmentioning
confidence: 99%